The Influence of B-SE on the Health Behavior of Santri Islamic Boarding School Related to Dengue Fever Prevention - Dewi, Novela Eka Candra; Safitri, Siti Zulfiana; Putriyana, Sofiyatul; Andini, Sulis Cahya (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Dengue Hemorrhagic Fever (DHF) is a significant health issue in tropical regions, including Indonesia, particularly in environments like Islamic boarding schools with high population density and sanitation challenges. This study evaluates the effectiveness of Booklet-Self Education (B-SE) in improving knowledge and clean and healthy living behavior (PHBS) among students for DHF prevention. Using a quasi-experimental pretest-posttest group design, 204 female students were divided into experimental and control groups, each with 102 participants. The experimental group received B-SE-based health education. Results revealed a significant improvement in the knowledge and PHBS practices of the experimental group, with a p-value of 0.000 (p<0.05). These findings highlight the potential of B-SE as an effective educational tool for fostering PHBS and preventing DHF in boarding school settings. The study suggests that incorporating such educational media into health programs can reduce DHF prevalence and enhance public health awareness in similar environments.